Racial/Ethnic Differences in Non-Work at Work - Daniel S. Hamermesh; Katie R. Genadek; Michael C. Burda (Institute of Labor Economics (IZA), 2017)
Evidence from the American Time Use Survey 2003-12 suggests the existence of small but statistically significant racial/ethnic differences in time spent not working at the workplace. Minorities, especially men, spend a greater fraction of their workdays not working than do white non-Hispanics. These differences are robust to the inclusion of large numbers of demographic, industry, occupation, time and geographic controls. They do not vary by union status, public-private sector attachment, pay method or age; nor do they arise from the effects of equal-employment enforcement or geographic differences in racial/ethnic representation. The findings imply that measures of the adjusted wage disadvantages of minority employees are overstated by about 10 percent.
Keywords: J22; J15; J31; 330; time use; wage discrimination; wage differentials